“P6LAND”: An Educational Tool for Free Flaps - Ziolkowski, Natalia; Haykal, Siba (Journal of Reconstructive Microsurgery Open, 2023)
Background Microsurgical education requires both technical skill and didactic knowledge. Learners are frequently asked to describe free flaps and their knowledge tested in clinical work and during exams.Methods We have created an educational tool that will aid learners in remembering important information related to flaps.Results “P6LAND” which divides and organizes information into three parts: Preoperative considerations, Pedicle, Position, LANDmarks, Plane of dissection, Protection and Postoperative considerations.Conclusion The aim of this paper is to further describe this educational tool and to provide a compendium for the most common fasciocutaneous, muscle, perforator, and bone flaps based on the literature. This tool was also prevalidated among a group of learners.
Keywords: microsurgery; learning; education; free flaps; flap; surgery